Palliative stenting for malignant colorectal stenosis in the elderly. Issue 1 (30th September 2022) - Ohno, Masashi; Nishida, Atsushi; Nishino, Kyohei; Hirayama, Hisashi; Takahashi, Kenichiro; Morita, Yukihiro; Kishi, Yuki; Morita, Yasuhiro; Bamba, Hiromichi; Shiomi, Hisanori; Imaeda, Hirotsugu
Abstract: Objectives: Self‐expandable metal stents are widely used for the treatment of malignant colorectal stenosis (MCS). In elderly individuals with MCS, self‐expandable metal stents are often used as a palliative treatment, but prophylactic stent placement is not recommended. We investigated the efficacy and safety of self‐expandable metal stents for the elderly in a palliative setting, specifically in a prophylactic setting. Methods: Elderly patients with MCS who received a palliative stent (the stent group) or palliative stoma (the stoma group) were retrospectively enrolled between April 2017 and June 2022, and the prognosis and complication rates were assessed. Additionally, patients in the stent group were divided into symptomatic and asymptomatic subgroups, and prognosis, stent patency, and complication rates were evaluated. Results: During the study period, 31 patients with a mean age of 85.4 years and 12 patients with a mean age of 82.0 years were enrolled in the stent and stoma groups, respectively. While overall survival and complication rates were comparable, the length of hospital stay was significantly shorter in the stent group. Of the 31 patients in the stent group, 16 asymptomatic patients received prophylactic stenting, which was not associated with increased complication rates. Conclusions: Palliative stents for MCS appear to be effective and safe even in the elderly, and thus, prophylactic stents can be considered for asymptomatic patients.